Chronic Ankle Instability Does Not Affect Lower Extremity Functional Performance - Demeritt, Kerry M. (attr, 2002)
Objective: To determine if functional performance is impaired in individuals with self-reported chronic ankle instability. Design and Setting: We used a between-groups design to assess 3 functional variables. All data were collected at a Division III college and a military academy. Before testing, all subjects performed a 5-minute warm-up, followed by a series of stretches for the lower extremity muscles. Subjects then performed cocontraction, shuttle run, and agility hop tests in a counterbalanced fashion. Three trials for each functional test were completed and averaged for analysis. Subjects: Twenty men with a history of at least 1 significant ankle sprain and episodes of at least 1 repeated ankle injury or feelings of instability or “giving way” were compared with 20 men with no prior history of ankle injury. Subjects were matched by age, height, weight, and activity level. Measurements: Time to completion was measured in seconds for the cocontraction and the shuttle run tests. The agility hop test was measured on an error point scale. Results: Using 3 separate, independent, 2-tailed t tests, we found no significant difference between groups for the cocontraction (P = .452), shuttle run (P = .680), or agility hop (P = .902) tests. Conclusions: Chronic ankle instability is a subjectively reported phenomenon defined as the tendency to “give way” during normal activity. Although athletes commonly complain of subjective symptoms associated with chronic ankle instability, our findings suggest that these symptoms do not negatively influence actual functional performance. Future researchers should evaluate other, more demanding functional-performance tests to further substantiate these findings.